Historical earthquakes and tsunamis of the South Ionian Sea occurring from 1591 to 1837 - PAPADOPOULOS, G. A.; PLESSA, A. (Bulletin of the Geological Society of Greece, 2001)
We improve the historical earthquake catalogue of the south Ionian Sea by critically reviewing twelve earthquake events occurring in the time interval 1591-1837. For some of them we complete historical information while for others we present information not taken into account in previous seismological studies. The procedure of réévaluation concluded with significant results. For example, the 5 May 1622 earthquake in Zakynthos , considered so far as a large destructive event, proved to have been only a felt event without any destructive effects, while the strong shocks of 21 August 1591 and 28 October 1766 (O.S.) are new events in the seismological literature. Tsunami phenomena reported in association with particular earthquakes also were reevaluated. It is shown that the large earthquake of 29 December 1820 in Zakynthos was not followed by a destructive tsunami flooding, as thought by previous authors, while evidence is presented that the sea-wave reportedly occurring in the Corinth Gulf in association with an aftershock of the above earthquake on 6 January 1821 very likely was not a tsunami but a storm surge that attacked the coast of Patras. The results obtained are of importance for the seismic and tsunami hazards assessment in the Ionian Sea.